Development of Cracker Supplemented with Jasmine Rice Bran Powder - วรชุม อินเกต โสรัจ; ภู่จันทร์ ผกาวดี (Journal of Food Health and Bioenvironmental Science, 2017)
The research aimed to develop a cracker product with enhanced nutrition, to study consumer’s acceptance, and to explore chemical composition of the product by using jasmine rice bran powder supplement of 15, 25 and 35 percent of the starch weight. The result of the 100 consumers’ acceptance study show that the customer’s highest satisfaction value was for the product with 25 percent jasmine rice bran powder supplement, with no significant difference compared to the 15 percent jasmine rice bran powder supplement. The 25 percent jasmine rice bran powder supplement had increased nutritional value of protein, fat, carbohydrate, fiber, Vitamin B1, and Vitamin B3; the fiber increased by 31.48 percent from the normal composition. From the study of the chemical composition, it was indicated that the 100 grams of the product with 25% jasmine rice bran powder supplement was comprised of protein 15.71±0.10%, carbohydrate 66.95± 0.12%, fat 8.24±0.11%, moisture 6.81±0.06%, ash 2.29±0.09%, fiber 4.32±0.07 grams, vitamin B1 1.68±0.13 mg. and vitamin B3 0.19±0.10 mg. Increasing jasmine rice bran powder in volume resulted in a slightly increased aw value of the product, and reduced the brightness. Moreover, the product was darker and had a higher crispy value. The microbial quality complies with the standard of community products. This research it created a functional food cracker, high in vitamins and fiber, for health-conscious consumers